Antiviral Agents against Omicron Subvariant BA.4.6 In Vitro - Walker, Jill; Schnell, Gretja; Kerr, William; Uraki, Ryuta; Imai, Masaki; Kawaoka, Yoshihiro (The New England journal of medicine, 2023)
To the Editor: Studies have shown that the neutralization activity of antibodies such as S309 (the precursor of sotrovimab) or sotrovimab, which bind outside the receptor-binding motif (RBM), depends on the expression level of the SARS-CoV-2 receptor (angiotensin-converting enzyme 2 [ACE2]), whereas the activity of RBM-targeting monoclonal antibodies is not considerably affected by ACE2 receptor expression. 1,2 Three recent letters in the Journal from a group at the University of Tokyo (Aug. 4 and Dec. 1, 2022, and Jan. 5, 2023, issues) 3-5 reported substantial loss of in vitro neutralization activity with S309 against recent B.1.1.529 (omicron) variants. This group cites the . . .